The Effects of Coronary Artery Bypass Grafting on Postural Balance - Sara Abolahrari-Shirazi; Farahnaz Emami; Zahra Rojhani-Shirazi; Mansour Janati; Mersa Razeghi (Shiraz University of Medical Sciences, 2022)
Background: Coronary Artery Bypass Graft (CABG) surgery is associatedwith several complications. Balance disorders have been reported in patients.The impairments were associated with fall-related injuries and increase thepossibility of morbidity, mortality, and healthcare costs. The present studyaimed to compare postural balance before and after CABG surgery in patientswith established coronary artery disease.Methods: This cross-sectional study was conducted on 87 patients aged 45-65years who had undergone CABG surgery through the great saphenous vein.Participants were enrolled into the study by convenience sampling. To assessstatic balance, individuals were asked to perform the Single Leg Stance Test(SLST). In addition, dynamic balance was measured by the Y-balance test, andthe Functional Reach Test (FRT) was conducted before and after CABG surgery.These clinical tests were performed during the week before surgery and repeatedone month after that. Paired t-test was used to compare the Y-balance scores,and Wilcoxon test was used to compare the mean values of other outcomesbefore and after CABG surgery. A level of P<0.05 was considered statisticallysignificant.Results: The results revealed a significant decrease in static and dynamic balanceafter CABG surgery (P<0.001). A significant reduction was also observed in themean FRT scores in the postoperative period (P<0.001).Conclusion: CABG surgery through the great saphenous vein influencedbalance in patients with coronary artery disease.